8. EVALUATION OF THE RESULTS OF PATIENT CARE AFTER ENDOSCOPIC SINUS SURGERY AND SOME RELATED FACTORS AT THE ENT DEPARTMENT OF TRANSPORT HOSPITAL IN 2024-2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the results of patient care after endoscopic sinus surgery and some related factors at the ENT Department of Transport Hospital.Subjects and methods: The study was conducted on 58 people treated with endoscopic sinus surgery and anal care at the Department of Otorhinolaryngology, Department of Transport from April 2024 to April 2025. Using a cross-sectional descriptive method, possible.Results: Patients aged 46-60 years old used the most (34.5%), male gender used 61.2% more than female. Number of people who demonstrated before nose surgery: 91.4%; 86.2% of patients had a nose piercing, 98.3% of patients had a pointed nose, 72.4% of patients had nasal polyps and 65.5% of patients had a septum. Care results: 87.9% of patients had good care. There was a relationship between age, pain status and good care outcomes, the results were statistically significant with P
Keywords: Endoscopic surgery, care results